"Mukbang Syar’i" Advertising Content: Representation and Reputation Trough Digital Communication - Rohimah, Afifatur (Jurnal Komunikasi Nusantara, 2025)
The phenomenon of "Mukbang" shar’i has become a habit on Instagram. This is done to avoid the negative stigma of society as a devoted Muslim. This study employed a critical discourse analysis method to reveal the representation behind the advertising content of "mukbang" advertising content by women in hijab. Researchers promise the discovery of a reality in a "mukbang" advertising content by dismantling the relationship of signs and texts with the context in society. This study presents the women in hijab who perform “mukbang” become proof of the existence of a Muslim in a competition dominated by non-Muslim broadcasts jokey. The discourse of resistance is depicted in a text with an irony theme to avoid netizens' negative stigma. The application of Islamic courtesy as a form of representation of self-image as a good and moral Muslim. The better the self-image is formed, the better the reputation is in endorsement. Abstrak Fenomena “Mukbang” syar’i sudah menjadi kebiasaan di Instagram. Hal ini dilakukan untuk menghindari stigma negatif masyarakat sebagai seorang muslim yang taat. Penelitian ini menggunakan metode analisis wacana kritis untuk mengungkap representasi dibalik konten iklan konten iklan “mukbang” yang dibawakan oleh perempuan berhijab. Peneliti menjanjikan penemuan realitas dalam sebuah konten iklan “mukbang” dengan membongkar hubungan tanda dan teks dengan konteks di masyarakat. Penelitian ini menghadirkan perempuan-perempuan berhijab yang melakukan “mukbang” menjadi bukti eksistensi seorang muslim dalam sebuah kompetisi yang didominasi oleh tayangan-tayangan non-Muslim yang bersifat lawakan. Wacana perlawanan tersebut tergambar dalam teks bertema ironi untuk menghindari stigma negatif warganet. Penerapan sopan santun Islami sebagai bentuk representasi citra diri sebagai seorang muslim yang baik dan bermoral. Semakin baik citra diri yang terbentuk maka semakin baik pula reputasinya dalam endorsement.